2008
DOI: 10.5194/bg-5-421-2008
|View full text |Cite
|
Sign up to set email alerts
|

Leaf area controls on energy partitioning of a temperate mountain grassland

Abstract: Abstract.Using a six year data set of eddy covariance flux measurements of sensible and latent heat, soil heat flux, net radiation, above-ground phytomass and meteorological driving forces energy partitioning was investigated at a temperate mountain grassland managed as a hay meadow in the Stubai Valley (Austria). The main findings of the study were: (i) Energy partitioning was dominated by latent heat, followed by sensible heat and the soil heat flux; (ii) When compared to standard environmental forcings, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 66 publications
9
77
1
Order By: Relevance
“…Canopy structure and LAI regulate energy partitioning via their impacts on surface albedo, roughness and stand transpiration Hammerle et al 2008). Consistent with previous studies in semiarid steppes and grasslands (e.g.…”
Section: Temporal Dynamics Of Carbon Water and Energy Exchange And Tsupporting
confidence: 77%
See 1 more Smart Citation
“…Canopy structure and LAI regulate energy partitioning via their impacts on surface albedo, roughness and stand transpiration Hammerle et al 2008). Consistent with previous studies in semiarid steppes and grasslands (e.g.…”
Section: Temporal Dynamics Of Carbon Water and Energy Exchange And Tsupporting
confidence: 77%
“…For example, in mesic forests and grasslands, shoot growth strongly controls energy partitioning via its impact on eco-physiological processes (e.g. transpiration), surface albedo and roughness (Hammerle et al 2008). In boreal coniferous forests, low radiation and temperature are key factors limiting the energy dissipated as λE (Launiainen 2010).…”
Section: Biophysical Controls On Carbon Water and Energy Exchangementioning
confidence: 99%
“…We noted a lower efficiency in the annual radiation budget of alpine meadow compared with the lowland grasslands, which can receive even higher incident radiation [73,74]. The lower efficiency observed on this plateau is attributed to the much higher net longwave radiation compared with lowland grasslands or the global surface [75].…”
Section: The Effect Of Vegetation Characteristics On Etmentioning
confidence: 83%
“…Li et al (2006) also investigated the partitioning of surface energy in the grazing lands of Mongolia, and concluded that the energy partitioning was also controlled by vegetation dynamics and soil moisture availability, although soil heat flux is reportedly higher than latent heat flux in most instances. In a temperate mountain grassland in Austria, Hammerle et al (2008) found that the energy partitioning in this climatic region was dominated by latent heat flux, followed by sensible heat flux and lastly soil heat flux.…”
Section: Influence Of Weather Conditions and Seasonalitymentioning
confidence: 97%